Penggunaan Metafora dalam Bimbingan dan Konseling di Kalangan Siswa Sekolah Menengah Atas - Fauzia, Azni Nurul; Agustine, Tiara (IKIP Siliwangi, 2023)
Implementing guidance and counseling in schools aims to help students actualize themselves. In self-actualization, students need to get to know and understand themselves. In reality, in the service process, students often find it difficult to convey thoughts, experiences, and feelings directly. The purpose of writing this article is to find out the benefits of communication metaphors for students in providing guidance and counseling services, especially in exploring students' needs. Through the Systematic Literature Review (SLR) research design, relevant literature is collected, identified, studied, evaluated, and interpreted. The number of journals studied consisted of seven journals, which were journals that met the inclusion criteria. The results of the research concluded that metaphors in services can help students who have difficulty describing difficult experiences, and expressing thoughts and feelings through techniques such as writing and interviews. The results of the worsening metaphor also lead to changes in behavior for the better. The results of the study have implications as material for study in the field of guidance and counseling related to efforts to help students channel their needs, convey difficulties, and learn new behaviors to achieve optimal development.